Impact of chronic stress on periodontal health - Gunepin Mathieu; Derache Florence; Trousselard Marion; Salsou Bruno; Risso Jean-Jacques (EDP Sciences, 2018)
Introduction: Periodontal diseases are caused by pathogenic microorganisms that induce increases in of local and systemic proinflammatory cytokines, resulting in periodontal damage. The onset and evolution of periodontal diseases are influenced by many local and systemic risk factors. Educational objective: In this article, we aim to review the results of the research on the impact of chronic stress on the occurrence, development, and response to periodontal disease treatments and on the pathophysiological mechanisms of periodontal disease. Conclusion: Chronic stress has a negative impact on the occurrence, development, and response to the treatment of periodontal disease via indirect actions on the periodontium. This can result from behavioral changes caused by stress (poor dental hygiene, smoking, etc.) and a direct neuroimmunoendocrinological action related to the consequences (particularly immunological) of the secretion of certain chemicals (e.g., cortisol) induced by the activation of the hypothalamus and the autonomic nervous system in response to stress. These factors necessitate multidisciplinary management (e.g., physician, oral surgeon, and psychologist) of patients to identify subjects with chronic stress and to employ countermeasures to decrease the impact of stress on the periodontium.